Geo Tourism : transforming Gunung Lang Recreational Park as geo park through geological and ecological Approach - Mustafa Kamal, Nur Muhamad Firdaus (2018)
The Geo Park Lembah Kinta has set initiatives to entitle as international geo park site. Meanwhile the identified site in Perak has a high geo tourism value in terms of geo heritage, geo cultural and geo formation. From this geo sites, procedures has been made to take place of the geo assets. Also the geological of Perak is dominated by limestone hills that which make some of the geo sites suitable to be enhance as Geo Park. The UNESCO Global Geo Park defines that the Geo Park concept is derived from the development of geological diversity and the need to conserve geological heritage. It is more focused on preserving, conserving and maintaining this valuable assets for the use of future generations. However, one of geo sites in Perak has been identified to meet the Geo Park requirements. The Gunung Lang Recreational Park, an urban escape park with serene nature backdrop with natural limestone hills. The Gunung Lang Recreational Park has the potential to be main Geo Park Center for Geo Park Lembah Kinta. This is because the GLRP itself is a tourism hotspot during the ‘Tahun Melawat Perak 2017’ which set by Department of Tourism Perak. The site study has a good positive feedback from both local and tourist, unfortunately the uniqueness of GLRP were not outstand among community of Ipoh. Through geological and ecological approach, GLRP can become a successful Geo Park for Geo Park Lembah Kinta. Thus, the awareness and interest of geo tourism will lift the community lifestyle and tourism sector in Perak.